Using virtual worlds for collaborative business process modeling - Brown, Ross; Recker, Jan; West, Stephen (Business process management journal, 2011)
Purpose - Process modeling is a complex organizational task that requires many iterations and communication between the business analysts and the domain specialists. The challenge of process modeling is exacerbated, when the process of modeling has to be performed in a cross-organizational, distributed environment. This paper aims to suggest a three-dimensional (3D) environment for collaborative process modeling, using virtual world technology.Design methodology approach - The paper suggests a new collaborative process modeling approach based on virtual world technology. It describes the design of an innovative prototype collaborative process modeling approach, implemented as a 3D Business Process Modeling Notation (BPMN) modeling environment in Second Life. We use a case study to evaluate the suggested approach.Findings - Based on a case study application, the paper shows that our approach increases user empowerment and adds significantly to the collaboration and consensual development of process models even when the relevant stakeholders are geographically dispersed.Research limitations implications - The paper presents design work and a case study. More research is needed to more thoroughly evaluate the presented approach in a variety of real-life process modeling settings.Practical implications - The research outcomes as design artifacts are directly available and applicable by business process management professionals and can be used by business, system and process analysts in real-world practice.Originality value - This research is the first reported attempt to develop a process modeling approach on the basis of virtual world technology. It describes a novel and innovative 3D BPMN modeling environment in Second Life.